IGF1R promotes radiation-induced HSCs activation by regulating DNA-PKcs-mediated DNA damage repair - Lin, Jiguo; Zhao, Gang; Feng, Jie; Sun, Chaonan; Liu, Chang; Li, Jiajing; Shen, Yannan; Cheng, Yunyun (Frontiers in Cell and Developmental Biology, 2025)
Introduction Ionizing radiation (IR)-induced liver fibrosis is one of the most serious complications of radiotherapy for liver cancer, and the core of its development lies in the activation of hepatic stellate cells (HSCs). The insulin-like growth factor 1 receptor (IGF1R) is commonly known as a growth-promoting kinase receptor that plays a critical role in cell differentiation and tissue reorganization, as well as in promoting the activation of HSCs, tentatively. Additionally, there has been a resurgence of interest in its role in DNA damage repair; nevertheless, the underlying mechanism remains poorly understood. Considering that DNA damage and repair are the most serious radiation injury events, the aim of this study was to explore the mechanism of IGF1R in the activation of HSCs by regulating DNA damage repair.Method and resultsIn this study, we first confirmed that IR induced the activation of HSCs, along with DNA damage and the upregulation of DNAdependent protein kinase catalytic subunit (DNA-PKcs) and IGF1R expressions. Then we indicated that the radiation-induced activation of HSCs and DNA damage repair were promoted by the activation or overexpression of IGF1R, either alone or together with DNA-PKcs activation, mechanistically through IGF1R–DNAPKcs interactions. The process is primarily facilitated by the nuclear translocation of IGF1R, which promotes PRKDC transcription at the mRNA level. Moreover, it involves an interaction with DNA-PKcs in the cytoplasm at the protein level, which, in turn, facilitates the entry of DNA-PKcs into the nucleus and subsequent promotion of DNA damage repair.DiscussionOur findings suggest that the inhibition of the IGF1R-promoted, DNA-PKcs-dependent non-homologous end joining (NHEJ) repair mode is a promising strategy to prevent the activation of HSCs. To the best of our knowledge, the present study is pioneering in its exploration of the mechanism by which IGF1R mediates radiation-induced activation of HSCs by regulating DNA-PKcs.